Correction to: the Post-Pandemic World: between Constitutionalized and Authoritarian Orders – China’s Narrative-Power Play in the Pandemic Era (Journal of Chinese Political Science, (2020), 10.1007/s11366-020-09695-3) - Chang, Yung-Yung (Journal of Chinese Political Science, 2020)
The original version of the article missed to add two references concerning method added to the main text and in the reference list. Following are the changes on page 3 of the original version as well as the details of the two missing references. The subsequent reference citations were also adjusted accordingly in the original version. In terms of method, this article will rely on a two-level document analysis of state documents, policy speeches, newspapers, magazine articles and (social) media accounts [8]. The first level involves a systematic review of news articles, journals and literature on Chinese narrative power and changing world order. With insights derived from this review, related primary documents such as official statements, speeches, policy proposals, and interviews delivered by government/officials/media outlets (particularly relevant to the COVID-19 crisis) will be investigated [8]. Besides this, social media (Twitter, YouTube, et cetera) will be used as an auxiliary resource because the pandemic is a current and ongoing issue and the role of social media in narrative discussion should not be ignored.1 Then the second level, the discourse analysis, will be integrated with knowledge derived from the first level to establish the “interweaving links between the texts and the…contexts” ([8, 9]:1756). The original article has been corrected.
CRIS-Team Scopus Importer:2020-12-11

RESPONSIBILITY AS AN OPPORTUNITY China's water governance in the Mekong region - Chang, Yung-Yung (The Routledge Handbook on Responsibility in International Relations, 2022)
CRIS-Team WoS Importer:2022-08-19

The Post-Pandemic World: between Constitutionalized and Authoritarian Orders – China’s Narrative-Power Play in the Pandemic Era - Chang, Yung-Yung (Journal of Chinese Political Science, 2020)
The paper aims to address the development of China’s narrative power during the COVID-19 pandemic and its impact on world order. It argues that in the post-pandemic world, the emergence of the authoritarian sub-order would be prompted by China’s more proactive narrative power, given that the climate of opinion is ambiguous when faced with the uncertainty of the pandemic. (This does not imply the end of the existing liberal order; instead, it features the coexistence of both orders.) To understand how China’s narrative power has encouraged the emergence of the authoritarian sub-order to coexist in parallel with the dominant constitutional order, the article first reviews the existing literature concerning the changing world order. In this section, it also briefly defines and differentiates between the constitutional and authoritarian orders, what defines world order, and what distinguishes authoritarian from constitutional liberal order. Second it looks at the theoretical grounding. The nature, role and power of narratives are explored. Ideas about strategic narratives and the economics of attention are discussed. This theoretical background paves the way to examine China’s narrative power during a pandemic. Lastly, it switches to the Chinese perspective to address its support for the plurality of orders and its awareness of the strength of narrative in influencing dominant ideas. It looks at how China’s narrative power has been exercised from three perspectives (formation, projection and reception). Here, it mainly tackles how China has used its narrative power to spin the pandemic to its advantage in the reorganization of world order: improving its international image and advocating the authoritarian order as an alternative. China has been building its narrative along with its changing strategic diplomacy – from restrained and low-profile to proactive and assertive. In the conclusion, some reflections on China’s narrative power and the implications for world order are considered.
CRIS-Team Scopus Importer:2020-10-23
Keywords: (Dis)information; Authoritarianism; China; COVID-19 pandemic; Foreign diplomacy; Narrative power; Soft power; Strategic narratives; World order